Integrating Blended Active Teaching Learning Approach for DBMS Lab Course - Jadhav, Priyanka; Patil, Pragati; Chaudhari, Nandini; Bedage, Sanmati (Journal of Engineering Education Transformations, 2025)
Data centralization, effective data management, and data access for application programs are all made simple by organizations by the database management system (DBMS) software. The role of DBMS is to provide an interface between physical data files and application programs. The use of the DBMS in the development of major applications and systems is essential. Currently, a number of big companies, nationally as well as globally, use databases as a backup for their application systems. Many highly well-known DBMS exist, including Oracle, Microsoft SQL Server, MySQL, PostgreSQL, Microsoft Access, IBM DB2, and many others. This paper aimed to evaluate Project based learning, WRITE Method, Concept Map and use of online tools like innovative teaching and learning techniques to help students develop their problem-solving techniques while taking the DBMS Laboratory Course. The outcome analysis calculated at the end of the semester Shows that student grades have improved significantly. Also, major changes in calculated and examined attainment of the course outcomes. Many students show observable improvement as a result of the adoption of various creative teaching and learning techniques.